Demokrasi Pancasila: Landasan Nilai Dan Prinsipnya Dalam Membangun Sistem Dan Etika Politik Indonesia - Ach. Fadlail (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2024)
This article discusses the basic values ​​and principles of Pancasila democracy, which is a nation-state view of life at the level of life, including in politics. Pancasila democracy consists of ethical and moral values ​​related to the values ​​of divinity, humanity, unity, democracy and justice, all of which reflect Indonesia's character and identity. These values ​​are expected not only to function as normative guidelines, but must also be implemented in state life, including ethical norms and legal norms in democracy. Pancasila also acts as the philosophical basis of the state, goes beyond the constitution, and becomes a reference in decision making by the government and state institutions. This research emphasizes the importance of Pancasila in forming noble character, love of the country, and creating an ethical political life for the common welfare of all Indonesian citizens. In a legal context, Pancasila establishes Indonesia as a rule of law state where all citizens are equal before the law, with the Constitutional Court as the institution tasked with overseeing the constitution and constitutional practices.